The Distribution of Paediatric Forearm Fractures: A Five-Year Retrospective Cohort Study of 4546 Forearm Fractures in Children - Hans-Christen Husum; Søren Kold; Ole Rahbek (Children)
Background: Forearm fractures are the most common fractures in children, accounting for 41% of all paediatric fractures. Most research focuses on distal forearm fractures, but studies encompassing the entire forearm are limited. Objective: This retrospective study describes the distribution and patterns of paediatric forearm fractures over a five-year period. Methods: We conducted a retrospective cohort study of children aged 0–15 years who received a radiograph of the forearm, wrist or elbow between March 2019 and December 2023 in the study region. Fractures were manually identified and registered from radiological reports. Fracture location, type (complete/incomplete), and epiphyseal involvement were analyzed across different age groups. Statistical analysis was performed using chi-square tests and descriptive statistics. Results: We identified 4547 forearm fractures from 4291 children. The median age was 10 years, and 57% of the patients were male. Fracture patterns varied significantly across age groups (p < 0.001), with older children experiencing more distal, complete, radial, and epiphyseal fractures. Younger children had a higher proportion of incomplete fractures and fewer distal or epiphyseal fractures. No significant differences in Salter–Harris classifications were found between age groups (p = 0.69). Conclusions: Fracture patterns in paediatric forearm fractures vary with age, with older children showing a higher incidence of complete, distal, and epiphyseal fractures. This study provides a detailed characterization of paediatric forearm fractures, which may inform clinical management and preventive strategies, particularly in tailoring age-specific care. Further research should explore the long-term outcomes of these fracture patterns.